2017
DOI: 10.1101/gad.291195.116
|View full text |Cite
|
Sign up to set email alerts
|

Loss of maternal Trim28 causes male-predominant early embryonic lethality

Abstract: Global DNA demethylation is a hallmark of embryonic epigenetic reprogramming. However, embryos engage noncanonical DNA methylation maintenance mechanisms to ensure inheritance of exceptional epigenetic germline features to the soma. Besides the paradigmatic genomic imprints, these exceptions remain ill-defined, and the mechanisms ensuring demethylation resistance in the light of global reprogramming remain poorly understood. Here we show that the Y-linked gene Rbmy1a1 is highly methylated in mature sperm and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…TRIM28, previously known as Krüppel-associated box-associated protein 1, is a nuclear corepressor for kruppel-associated box domain-containing zinc finger proteins 18. TRIM28 participates in many aspects of cellular biology, either promoting proliferation or leading to anti-proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM28, previously known as Krüppel-associated box-associated protein 1, is a nuclear corepressor for kruppel-associated box domain-containing zinc finger proteins 18. TRIM28 participates in many aspects of cellular biology, either promoting proliferation or leading to anti-proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As well as paternally imprinted loci and endogenous retroviruses, individual genes in the paternal genome resist demethylation; for example, the Y chromosome gene Rbmy1a1 in the mouse. The zygotic expression of this gene is repressed by sperm-inherited DNA methylation of its promoter, which has been demonstrated by the loss of methylation, ectopic expression, and periimplantation lethality of male embryos in the absence of maternal TRIM28 (Sampath Kumar et al 2017). In the near future, the catalogue of regions resistant to reprogramming will probably expand with development of the miniaturisation of sequencing technologies and growth in the number of studies on the DNA methylation landscape of embryos.…”
Section: Postfertilisation Reprogramming Of the Sperm Dna Methylomementioning
confidence: 99%
“…Tripartite motif-containing 28 (TRIM28), also known as KAP1 and TIF1β, is required for the maintenance of genomic imprinting [ 6 , 58 , 59 ]. TRIM28 is a maternal-effect protein, as indicated by the highly early embryonic lethality resulting from the dysregulation of genomic imprinting in mice lacking maternal TRIM28 [ 59 , 60 ]. It has also been reported that maternal TRIM28 not only maintains DNA methylation at germline imprints during early genome-wide reprogramming, but also regulates DNA methylation at imprinted gene promoters after genome-wide reprogramming [ 61 ].…”
Section: Resultsmentioning
confidence: 99%